2014
DOI: 10.1093/pcp/pcu052
|View full text |Cite
|
Sign up to set email alerts
|

The Sugar Transporter Inventory of Tomato: Genome-Wide Identification and Expression Analysis

Abstract: The mobility of sugars between source and sink tissues in plants depends on sugar transport proteins. Studying the corresponding genes allows the manipulation of the sink strength of developing fruits, thereby improving fruit quality for human consumption. Tomato (Solanum lycopersicum) is both a major horticultural crop and a model for the development of fleshy fruits. In this article we provide a comprehensive inventory of tomato sugar transporters, including the SUCROSE TRANSPORTER family, the SUGAR TRANSPOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
105
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 92 publications
16
105
0
1
Order By: Relevance
“…The expression of SUT in leaves has been shown to differ markedly for different family members (Weise et al, 2000;Payyavula et al, 2011;Reuscher et al, 2014). The comparison of SUT expression levels under control conditions is in line with previous results, generally showing the SUT responsible for phloem loading as having the highest level of expression (Fig.…”
Section: Cross-platform Comparison Of Transcriptomics Data Provides Csupporting
confidence: 90%
“…The expression of SUT in leaves has been shown to differ markedly for different family members (Weise et al, 2000;Payyavula et al, 2011;Reuscher et al, 2014). The comparison of SUT expression levels under control conditions is in line with previous results, generally showing the SUT responsible for phloem loading as having the highest level of expression (Fig.…”
Section: Cross-platform Comparison Of Transcriptomics Data Provides Csupporting
confidence: 90%
“…For example, such studies have led to the identification of putative Receptor-like Kinases (RLKs) (Sakamoto et al, 2012), putative SUN, OFP, GABBY, transcriptions factors (Huang et al, 2013), 146 putative ERF proteins (Pirrello et al, 2012), ERECTA genes (Villagarcia et al, 2012), and MAPK (Kong et al, 2012), helicase (Xu et al, 2013), WRKY (Huang et al, 2012), and nucleobase-ascorbate transporter (NAT) gene family members (Cai et al, 2014). With a comprehensive inventory of all sucrose and monosaccharide transporters encoded in the tomato genome, Reuscher et al (2014) identified 52 genes putatively encoding sugar transporter proteins in the tomato reference genome. All these sugar transporter protein families belong to the MFS family which is characterized by 12 transmembrane domains (TMDs) and driven by the protonmotive force.…”
Section: Discussionmentioning
confidence: 99%
“…These transporters are characterized by 12 transmembrane domains (TMDs) (Doidy et al, 2012;Reuscher et al, 2014). The plant SWEET (Sugars Will Eventually be Exported Transporters) family of sugar transporters is a recently identified seven-TMD protein family (PFAM code PF0383) Xuan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Of the soluble solids, approximately 60% are sugars, mainly glucose and fructose (Gómez and Camelo, 2002), since the plant is highly necessary an adequate supply of these, nutrition and management are very important to achieve this goal (Reuscher et al, 2014). Among other important factors, nutrition is essential for an adequate concentration of °Brix in marketable fruits.…”
Section: Resultsmentioning
confidence: 99%
“…De los sólidos solubles, aproximadamente 60% son azucares, principalmente glucosa y fructosa (Gómez y Camelo, 2002), dado que en la planta es altamente necesario un suministro adecuado de estos, la nutrición y manejo son muy importantes para lograr tal fin (Reuscher et al, 2014). Entre otros factores de importancia, la nutrición es fundamental para una adecuada concentración de °Brix en frutos comercializables.…”
Section: Resultsunclassified